Penerapan Pendidikan Adab di MTs Al Kahfi Surakarta - Yaman, Nur; Yadi, Yadi; Anshory, Muhammad Isa (TSAQOFAH, 2025)
This study aims to describe the implementation of character education (adab) at MTs Al Kahfi Surakarta and analyze the roles of teachers and the school environment in shaping students’ character comprehensively. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings reveal that character education is integrated into the curriculum through subjects such as Akidah Akhlak and is implemented through daily practices within the school environment. Teachers serve as role models and mentors using a holistic approach, while the school environment fosters an atmosphere conducive to the development of refined character. Nevertheless, challenges remain, including inconsistent application of adab values by students outside of school and the negative influence of social media. The study recommends the development of a continuous character education curriculum and the strengthening of collaboration between schools and families to support the character-building process. Overall, the implementation of character education at MTs Al Kahfi Surakarta is considered effective and positively impacts students' character development.